Matters of survival: a case of heavy handed didactic moralism in Ndau cautionary folktales - Chigidi, Willie (Taylor and Francis Online, 2022)
This paper discusses the Ndau folktale that has not received scrutiny from scholars who have invested resources in studying oral literature of the Zimbabwean people. During the years that Ndau was regarded as a Shona dialect it occupied the most peripheral position and its oral traditions were equally marginalized. This writer posits that in Ndau folklore there is a type of folktale that served to conscientize Ndau people about their historical circumstances for the sake of their safety and security. The researcher identifies folktales that reflect the history of Ndau labor migrations and Ndau experiences during Nguni raids. The writer concludes that the origins of this type of folktale, which is not found in the tales of the other Shona people of whom the Ndau were part up to 2013, is to be sought in the history and existential circumstances of the Ndau people themselves. The writer selects three folktales to illustrate risks faced by those who traveled to South African mines, cases of sexual infidelity during the long periods of spousal separation, and the dangers that befell locals during times of Nguni raids.